Psychosocial Impact and Quality of Life in Children with Strabismus - Bima Ryanda Putra (Sriwijaya Journal of Ophthalmology, 2022)
Strabismus is a condition due to misalignment of the visual axis of the eyes, also known as a squint. Squint eyes can be clearly seen by others, and give symptoms such as double vision or blurred vision. In a systematic review study revealed that 1 in every 50 people suffer from strabismus, and this disorder greatly affects their quality of life. Psychological impacts on people with strabismus can be caused by environmental factors, such as the non-acceptance of strabismus sufferers in the social environment. If strabismus is not treated in a timely manner in children, besides cosmetic consequences, it can have a dramatic impact on learning abilities, impairing their physiological and psychological performance, ultimately affecting their development and maturity. In particular, a positive effect of strabismus surgery has been demonstrated post strabismus surgery.